Enzyme‐responsive macrocyclic metal complexes for biomedical imaging - Quoc‐Viet Le; Jaiwoo Lee; Seungbeom Ko; Hyunjung Kim; Thien Y Vu; Yearn Seong Choe; Yu‐Kyoung Oh; Gayong Shim (Bioengineering & Translational Medicine, 2023)
Abstract Metal chelator‐based contrast agents are used as tumor navigators for cancer diagnosis. Although approved metal chelators show excellent contrast performance in magnetic resonance imaging (MRI), large doses are required for cancer diagnoses due to rapid clearance and nonspecific accumulation throughout the body, which can compromise safety. The present study describes an enzyme‐responsive metal delivery system, in which enzyme overexpressed in the tumor microenvironment selectively activates the tumor uptake of gadolinium (Gd). Gd was loaded into enzyme‐responsive macrocyclam (ErMC) modified with a PEGylated enzyme‐cleavable peptide resulting in Gd@ErMC. The PEGylated shell layer protected Gd@ErMC from nonspecific binding in the blood, increasing the half‐life of the contrast agent. Specific cleavage of the PEGylated shell layer by the enzyme selectively liberated Gd from Gd@ErMC at the tumor site. Evaluation of the in vivo distribution of Gd@ErMC in tumor‐bearing mice by MRI and positron emission tomography (PET) showed that Gd@ErMC had an extended half‐life and was highly specific. Histological and serological analysis of Gd@ErMC‐treated mice showed that this agent was safe. This novel enzyme‐responsive contrast agent delivery system shows promise as specific theranostic agent for MR‐guided radiotherapy.